Urban Transport in Mandalay : Institutions, Expenditures, and Funding - World Bank (World Bank, Washington, DC, 2020)
Mandalay is the second-largest city in Myanmar and a gateway to the Bay of Bengal to neighboring economic hubs. Rapid economic and demographic growth, paired with the relaxation of import restrictions for new and used two, three, and four-wheeler has resulted in rapidly declining conditions for urban transport. Motorization and vehicle intensity use, congestion, emissions, and traffic-related injuries are hampering well-being and competitiveness. Unless action is taken, Mandalay will consolidate as a motorcycle-only city, posing challenges for the excluded and vulnerable. The report calls for urgent actions to seize the window of opportunity brought by a growing economy and put forward actionable, simple, and affordable strategies aiming to provide efficient, equitable, clean, and safe mobility for Myanmar’ largest urban agglomerations. This overview note presents highlights of the report for Mandalay. It can support policy discussions on improving urban transport with proportional funding and financing and financing options suited to a bold vision for Mandalay.